Intrahousehold empowerment patterns, gender power relations, and food security in Uganda - Farzaneh Barak; Jackson Efitre; Robinson Odong; Hugo Melgar-Quiñonez (Wiley Periodicals LLC on behalf of Policy Studies Organization., 2024)
This study examined (a) the relationship between women’s empowerment, men’s empowerment, and food security within households and (b) the effect of gender power in households on the food security status of women and men in Uganda’s fishing villages using NutriFish project data (N = 762). An inaugural intersectional gender analysis approach applied the project-level Women’s Empowerment in Agriculture Index (pro-WEAI), categorizing indicators into five domains: decision making, labor sharing, resource access, norms and beliefs, and gender parity within households. Binary logit models were computed, including interactions between the empowerment of women and men, controlling for individual- and household-level characteristics, and stratified by gender and occupation (i.e., fishing vs. non-fishing) to account for context differences. Results showed that empowering women in nonfishing groups enhanced food security for both genders, regardless of men’s empowerment. In fishing groups, women’s food security improved most when their partners were already empowered, while men’s empowerment remained relatively unaffected. Notably, the norms and beliefs domain was strongly linked to food security, except for non-fishing men. Context-specificgender interventions and analyses are vital to address food security disparities and critical to informing project implementers and policymakers in gender- and nutrition-sensitive development projects to target the most vulnerable groups.
Keywords: context specific; food security; gender analysis; intersectionality; small-scale fisheries; Uganda; women’s empowerment